TRAINING TO STRENGTHEN EARLY READING TEACHING SKILLS USING THE SYLLABUS-BASED READING LEARNING MODEL FOR LOWER ELEMENTARY SCHOOL TEACHERS IN THE DISTRICT OF KAHAYAN TENGAH, PULANG PISAU REGENCY - Petrus Purwadi; Paul Diman; Alifiah Nurachmana; Albertus Purwaka; Misnawati; Patrisia Cuesdeyeni; Lazarus Linarto; Linggua Sanjaya Usop; Syarah Veniaty; Stefani Ratu Lestariningtyas; Nirena Ade Christy; Yulina Mingvianita; Ibnu Yustiya Ramadhan; Hana Pertiwi; Noraida; Nurlita Feblian (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
This community service program focuses on addressing the problem of low reading skills among lower grade students in Kahayan Tengah Subdistrict, Pulang Pisau Regency. Data from the Education Office (2023/2024) reveals that around 40% of third grade students in several elementary schools, such as in Bahu Palawa and Pamarunan, are not yet fluent in reading. This shows the urgency of improving teachers' capacity to deal with these learning difficulties. As a solution, a syllable learning model was introduced, designed to provide a systematic conceptual framework for letter recognition and word formation, thereby making it easier for students to achieve reading proficiency, which is also the foundation for writing. This reinforcement activity was carried out using a classic method that combined counseling, discussion, and hands-on practice. There were 38 participants, all teachers from the Hapakat Cluster 4 Teacher Working Group (KKG), which covers four elementary schools. Based on observations, 90% of the target participants successfully practiced the lessons well. Evaluation of the students showed an average score of 59.06 with a classical completeness of 25%, indicating the need for continuous intervention. The output of this program is an increase in teachers' knowledge and understanding in implementing early reading learning, which is expected to improve the quality of learning in the classroom. More broadly, the targeted final output is the publication of scientific articles in the PengabdianKu Journal of Muhammadiyah University Palangka Raya and the registration of Intellectual Property Rights .